CHANGE LEADERSHIP IN PROFESSIONAL SPORT– BASED ON INTERNATIONAL AND NATIONAL EXAMPLES - András, Krisztina; Máté, Tünde (Applied Studies in Agribusiness and Commerce, 2025)
Accelerated and turbulent changes – partly driven by external operating environment – are determining day-to-day operations and operational decisions of organizations. They need to be able to respond appropriately, in line with their strategy, yet proactively, in order to maintain competitiveness and future prospects. This is also the case in the world of sport. Our focus is on professional sport – on a domestic sport federation and on one of the most successful clubs in Hungary. The study attempts to adapt the change management theory to professional sport to make it strategic and proactive by creating adapted basis for change management rather than change. Primary and secondary sources were processed using qualitative methods. We investigated three areas of change management / leadership: financial strategy, organization of international sport events and facility management. We conclude that change leadership can be identified in practices of the sports organizations studied, and the theoretical framework can be adapted and applied.